2016
DOI: 10.19080/jaicm.2016.01.555556
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study Comparing Medical Student Intubation on Cadaveric and Manikin Models Using the King Vision™ Videolaryngoscope and Direct Laryngoscopy

Abstract: Objective: Compare intubation by medical students with direct laryngoscopy (DL) versus King Vision™ videolaryngoscope in training and cadaveric models.Methods: 24 medical students with no experience intubating humans were randomized into two groups: DL first or King Vision™ videolaryngoscope first. Following a short training, techniques were practiced ona manikin model. Intubation success, ease of use, and one timed manikin intubation was recorded. Students crossed, repeated training and trial with other techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…[111213] It may be because of the inappropriate method of insertion of VL or too distal insertion of blade tip leading to discordant alignment between glottis and path of ETT. [14] In our study we followed the recommended procedure of device use and found no difficulty in ETT insertion. The only problem with KVVL is fogging of distal lens affecting the image clarity.…”
Section: Discussionmentioning
confidence: 73%
“…[111213] It may be because of the inappropriate method of insertion of VL or too distal insertion of blade tip leading to discordant alignment between glottis and path of ETT. [14] In our study we followed the recommended procedure of device use and found no difficulty in ETT insertion. The only problem with KVVL is fogging of distal lens affecting the image clarity.…”
Section: Discussionmentioning
confidence: 73%